Coordination of Voluntary and Stimulus-Driven Attentional Control in Human Cortex. - Serences, John T.; Shomstein, Sarah; Leber, Andrew B. (Psychological Science., 2005)
A study was conducted to explore the neural basis of contingent attentional capture, a phenomenon where nontarget items in a visual scene that share a defining feature with the target of the visual scene can capture the viewer's attention. Findings revealed that attentional capture is accompanied by an increase in cortical activity in the corresponding regions of retinotopically organized visual cortex. Concurrent activation in the ventral frontal cortex and the temporo-parietal junction indicate that these regions coordinate voluntary and stimulus-driven attentional control settings in order to determine which stimuli compete for attention.